2023
DOI: 10.1002/jex2.84
|View full text |Cite
|
Sign up to set email alerts
|

A new isolation method for bacterial extracellular vesicles providing greater purity and improved proteomic detection of vesicle proteins

Abstract: Contaminants within cell culture media often co-isolate with eukaryotic extracellular vesicles (EVs) thus affecting their biological properties. It has yet to be investigated if this is also true for bacterial EVs (BEVs), especially for organisms grown in complex culture media containing animal-derived products. To address this question, we isolated BEVs from the fastidious bacterium Helicobacter pylori grown in either standard Brain Heart Infusion (BHI) medium or BHI depleted of animal-derived products (D-BHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…To minimise these effects, chemically defined media that is free of vesicle contaminants should be used. Alternatively, if rich media is necessary, vesicles should be depleted prior to use, as recently proposed (Le et al, 2023). By utilising a chemically defined media (BDMr6) this study demonstrates that B. thetaiotaomicron releases distinct sub-populations of vesicles.…”
Section:  Discussionmentioning
confidence: 67%
“…To minimise these effects, chemically defined media that is free of vesicle contaminants should be used. Alternatively, if rich media is necessary, vesicles should be depleted prior to use, as recently proposed (Le et al, 2023). By utilising a chemically defined media (BDMr6) this study demonstrates that B. thetaiotaomicron releases distinct sub-populations of vesicles.…”
Section:  Discussionmentioning
confidence: 67%
“…The BHI broth used as a bacterial growth broth in this study contains components from beef heart and calf brains and may include vesicles and vesicle‐like structures (Le et al, 2023). We did not find any vesicle‐like particles in the negative control samples with TEM, but we cannot conclude that the broth is vesicle‐free.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not possible to completely distinguish the different particle populations from each other (Giebel & Helmbrecht, 2017; Guerreiro et al, 2018). Le et al (2023) detected dark structures on TEM pictures of EV‐like particles (EVLPs) from BHI, but after using eukaryotic EV markers they concluded that the EVLPs in BHI probably are large protein aggregates and not true EVs. Finally, several other factors can affect the NTA results, among them the potential fusion of vesicles (Grava et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…C. jejuni EVs were isolated as described ( 33 ) with some modifications. In brief, C. jejuni strains were inoculated to an optical density (OD 600 ) of 0.1 in depleted Brain Heart Infusion (D-BHI; BD Bacto) broth containing Skirrow’s selective supplement and tetracycline (10 µg/mL) or kanamycin (20 µg/mL), as required.…”
Section: Methodsmentioning
confidence: 99%
“…EVs (100 µg/mL) were visualized by negative staining on the FEI Tecnai Spirit electron microscope (Fei Company), as described previously ( 33 ). Images were randomly selected across the grids at 42,000 x magnification.…”
Section: Methodsmentioning
confidence: 99%